Synthesis and Spectroscopic Investigations on Nickel(II) and Cobalt(III) Complexes of Dicyandiamide with 2-Alkoxyethanols (Alkoxy = Methoxy, Ethoxy or Butoxy); DNA Binding Interactions on Nickel(II) nitrate Complexes - Pramodini Devi, S.; Hemakumar Singh, R.K. (Asian Journal of Chemistry, 2010)
Ni(II) and Co(III) complexes of dicyandiamide in alkoxyethanols (alkoxy = methoxy, ethoxy or butoxy) were synthesized and characterized by elemental analysis, magnetic moment, conductance, IR, UV and 1H NMR spectral studies. In the 1H NMR spectra appearance of new multiplet peaks at 3.25-3.50 ppm assignable to CH3-O-CH2-CH2-O- for complex [Ni(II)(1-amidino-Omethoxyethylurea) 2](NO3)2 and 3.30-3.45 ppm due to CH3-CH2-O-CH2-CH2-O- for complex [Ni(II)(1-amidino-O-2-ethoxyethyl-urea)2](NO3)2, respectively suggests the addition of alkoxyethanols in complexation which is also supported by IR studies. The electronic spectral studies on Ni(II) and Co(III) complexes indicate square planar and octahedral structures, respectively. Fluorescence, UV absorption as well as thermal denaturation studies revealed that [Ni(II)(1-amidino-O-methoxyethylurea)2](NO3)2 and [Ni(II)(1-amidino-O-2-ethoxyethylurea) 2](NO3)2 complexes are avid binder to calf thymus DNA (CT-DNA).